Home-field advantage effect weakened over time but was strengthened by labile carbon input in later litter decomposition stage - Xue, Yafang; Ma, Ning; Jiang, Lei; Wang, Weimin; Li, Shenggong (Frontiers in Plant Science, 2025)
Home-field advantage (HFA) hypothesis proposes that leaf litter decays more rapidly in its original place than elsewhere owing to specific litter-field affinity. However, the HFA effect may vary over time and receive influences from other external factors, and it remains unclear whether the labile carbon (C) in root exudates influences the HFA effect during later decomposition stage. We aim to 1) elucidate how the HFA effect varies over time, 2) demonstrate how the HFA effect changes when stimulated by labile C at the later decomposition stage, and 3) explore how fungi affect the HFA effect. We conducted a reciprocal litter transplant experiment using two tree species, (Pinus elliottii and Cunninghamia lanceolata) with a two-phase design (early vs. late decomposition, plus glucose addition). We harvested the samples of soil and litter after decomposition for 1, 2, 4 and 6 months. Glucose (labile C) was added to soil after decomposition of 4 months. The HFA effect decreased over time, and the fungal community dissimilarity between home and away soils, especially Eurotiomycetes, affected variations in HFA. Additionally, glucose additions led to a significant increase of 15.19% in the HFA effect (p<0.05) during later decomposition stage, which was primarily associated with Sordariomycetes. Our findings implies that the HFA in litter decomposition was mainly associated with specific fungal taxa. Importantly, the introduction of labile C strengthened the HFA effect at later decomposition stage. Therefore, it cannot be overlooked that the priming effect of labile C input on the HFA effect at later decomposition stage in future research. Our two-phase design study further highlights the differences in litter decomposition between home and away soils at different decomposing stages and the regulation of HFA by specific fungal taxa and labile carbon inputs, especially in the later decomposition stage.